Typologia i ocena bioklimatu Polski na podstawie bilansu cieplnego ciała człowieka = Typology and evaluation of the bioclimate of Poland on the basis of the human body heat balance - Krawczyk, Barbara (1935– ) (IGiPZ PAN, 1993)
102, [2] s. : mapy, rys., err. ; 24 cm
Bibliogr. s. [92]-98
Streszcz. ang.
Keywords: bioklmat; typy bioklimatu; bilans cieplny ciała człowieka; Polska

Przegląd Geograficzny T. 73 z. 4 (2001) (IGiPZ PAN, 2001)
24 cm
Keywords: ubóstwo; miasta; geografia religii; rolnictwo; bilans cieplny ciała człowieka; bioklimatologia; burze; Poznań; Ukraina; Węgry; Dania

Economic use of the Babia Góra Massif and the assessment of anthropogenic changes in the course of the timberline - Łajczak, Adam; Lamorski, Tomasz (IGiPZ PAN, 2015)
In Poland’s Babia Góra Massif (the most elevated ridge in the Western Flysch Carpathians), and in the surrounding valleys, various kinds of economic use of natural resources have been engaged in the last 600 yearsor more. However, the most major changes in the natural environment here have taken place under the influence of grazing and forestry. Some such economic uses already represent forms of human activity that are nowhistory, their cessation being the prerequisite for a regeneration of vegetation that is now ongoing. One of the most visible effects of past grazing is a lowered timberline first and foremost coinciding with the more accessiblesouthern slope of the massif. In turn, on a small part of the steep northern slope degraded by grazing, avalanches have become active, along with debris flows of earlier times, both of which also served to fragmentforest. Protection of the Babia Góra Massif has brought the end to grazing referred to, and this has allowed for the progressive return of the timberline to its previous position. Overall, the work described here is basedon information from the literature, unpublished studies and maps dating back over the last 400 years.
24 cm
Keywords: gospodarcze użytkowanie gór; wypas; leśnictwo; górna granica lasu; Babia Góra; Polska; fliszowe Karpaty Zachodnie

Bilans cieplny ciała człowieka jako podstawa podziału bioklimatycznego obszaru Iwonicza = Teplovoj balans tela čeloveka kak osnova bioklimatičeskogo rajonirovaniâ kurorta Ivonič = Heat balance of the human body as a basis for the bioclimatic divide of the health resort Iwonicz - Krawczyk, Barbara (1935– ) (IGiPZ PAN, 1979)
71 s. : il. ; 24 cm
Bibliogr. s. 65-68
Streszcz. ang., ros.
Keywords: Bioklimatologia -- metodologia [KABA]; Bioklimatologia -- Polska -- Iwonicz-Zdrój [KABA]; Termoregulacja [KABA]; Iwonicz-Zdrój (Polska) -- klimat [KABA]; bioklimat; bilans cieplny ciała człowieka; uzdrowiska

Cylowa Zerwa landslide – debris flow forms on Mount Babia Góra (1725) and their development over the last ca. 150 years, Western Carpathians - Łajczak, Adam. Autor; Margielewski, Włodzimierz. Autor; Zielonka, Tomasz. Autor; Pasierbek, Tomasz. Autor; Lamorski, Tomasz. Autor; Kozina, Piotr. Autor; Izworska, Katarzyna. Autor (IGiPZ PAN, 2023)
Cylowa Zerwa landslide – debris flow located on the northern slope of Mt. Babia Góra (1725 m a.s.l.) within the 400 m wide altitude interval (1430-1024 m a.s.l.) is a knowable object which however has not been sufficiently noticed in geomorphological research. This paper, based on geomorphological, geological and dendrochronological investigations, as well as LiDAR data analysis, develops the following issues which describe the functioning of this object during the last ca. 150 years: Cylowa Zerwa in the gravity induced mass movements system of Mt. Babia Góra; relief of the landslide – debris flow and surrounding areas; stages of changes in limit and relief of the mass movement area during the last 150 years; relief elements of the Cylowa Zerwa which are related to debris flow; relationship between dates of the Cylowa Zerwa activation with annual spruce increments. The Cylowa Zerwa, as the only one among Mt. Babia Góra landslides studied, is distinguished by a clear bipartite relief – the upper segment is represented by rock packages, whereas landforms of the middle and lower segments are similar to those originated in the conditions of debris flow. The Cylowa Zerwa landslide – debris flow shows significant education values and it is a remarkable geotourist object.
24 cm
Keywords: Babia Góra; Zachodnie Karpaty Fliszowe; grzbiet homoklinalny; rzeźba strukturalna; osuwisko; spływ gruzowy; zniszczenia lasów; zakłócenia ruchu turystycznego; geoturyzm

Bioclimatic research of the human heat balance = Bioklimatyczne badania bilansu cieplnego człowieka - Błażejczyk, Krzysztof; Krawczyk, Barbara (1935– ) (IGiPZ PAN, 1994)
66 s. : mapy, rys., wykr. ; 29 cm
Bibliogr. s. 59-64
Streszcz. pol.
Keywords: Bioklimatologia -- modele matematyczne [KABA]; Bioklimatologia -- Polska [KABA]; Człowiek -- skutki oddziaływania klimatu -- Polska [KABA]; bilans cieplny ciała człowieka

Poszukiwanie wieloletniej zmarzliny i budowa geologiczna Babiej Góry w świetle wyników obrazowania elektrooporowego = Permafrost prospecting and geological structure of Mt. Babia Góra in the light of the electroresistivity imaging method - Dobiński, Wojciech; Glazer, Michał; Bieta, Barbara; Mendecki, Maciej J. (IGiPZ PAN, 2016)
W artykule przedstawiono wyniki prac nad hipotezą o występowaniu wieloletniej zmarzliny w okołoszczytowej okolicy Babiej Góry. W badanym obszarze wykonano trzy profile inwersyjnego obrazowania oporności, których maksymalna głębokość interpretacji sięga do około 90 m pod powierzchnię gruntu. Uzyskane wyniki nie potwierdzają jednoznacznie występowania permafrostu w badanym terenie, natomiast dobrze ukazują budowę geologiczną szczytowych partii Babiej Góry.
24 cm
Keywords: permafrost; Babia Góra; inwersyjne obrazowanie oporności

Zarys historii działalności gospodarczej w masywie Babiej Góry i otaczającym terenie (Zachodnie Karpaty) = An outline history of economic activity on Mt. Babia Góra and in the surrounding area (Western Carpathians) - Łajczak, Adam (IGiPZ PAN, 2016)
Na Babiej Górze i w jej otoczeniu, podobnie jak w sąsiednich masywach górskich, działalność gospodarcza rozpoczęła się w schyłkowym okresie średniowiecza. Poszczególne sposoby użytkowania zasobów przyrody były rozwijane w różnym czasie, niektóre z działań człowieka uległy zanikowi, podczas gdy inne nadal się rozwijają. Największe zmiany w środowisku przyrodniczym dokonały się pod wpływem gospodarki leśnej, która przez pewien czas była związana z lokalnym hutnictwem żelaza, a także w wyniku pasterstwa. Jednym ze skutków pasterstwa jest obniżenie górnej granicy lasu, które na większym obszarze objęło południowy, łatwiej dostępny stok masywu. Rozpoczęta w XIX w. gospodarka leśna dąży, pomimo nasilenia wyrębów lasu, do utrzymania wysokiego zalesienia masywu, a wynikiem wprowadzonych między 1926 i 1955 r. prawnych form ochrony przyrody jest przywracanie składu gatunkowego drzewostanów zgodnego z lokalnymi uwarunkowaniami siedliskowymi. Skutkiem usunięcia pasterstwa jest nadal trwająca progresja górnej granicy lasu. Praca bazuje na informacjach z literatury i materiałach archiwalnych.
24 cm
Keywords: pasterstwo; gospodarka leśna; Babia Góra; Karpaty

The diversity of soils of the upper forest line, transition, and mountain pine zones in the Babia Góra Massif - Nicia, Paweł; Zadrożny, Paweł; Czajka, Barbara (IGiPZ PAN, 2015)
The upper forest line transition zone up to the mountain pine zone on the southern slopes of Babia Góra, has diversified phytosociology and soils. The development and diversity of the upper forest soils are affectedby morphogenetic processes, physiographic conditions, vegetation, and anthropogenic factors which in the past included sheep grazing. An analysis conducted on the morphological and chemical soil properties in thetransects covering the upper forest line, transition, and mountain pine zone on the southern slopes of Babia Góra revealed considerable diversification characterising these soils within the individual altitude zones.A substantial changeability in the contents of the analysed components in the investigated soils is characteristic for mountain soils developed in the areas with great intensity of slope phenomena and processes.
24 cm
Keywords: Babia Góra; gleby; górna granica lasu

Typy źródeł i ich rozmieszczenie na Babiej Górze (Zachodnie Karpaty) = Types of springs and their location on Mount Babia Góra (Western Carpathians) - Łajczak, Adam (IGiPZ PAN, 2017)
Zanalizowano głębokość i zasięg krążenia wód podziemnych w wyróżnionych typach utworów wodonośnych na obszarze monoklinalnego grzbietu Babiej Góry, najwyższego w Beskidach Zachodnich. Najgłębsze krążenie wód obejmujące najdłuższe odcinki stoków zachodzi w rozległych osuwiskach na podłożu piaskowców magurskich w górnej części masywu. W kategoryzacji wypływów zastosowano następujące klasyfikacje źródeł: położenie geomorfologiczne (kierunek napływu wód podziemnych i sposób ich krążenia), rodzaj utworów wodonośnych, rozmieszczenie w skali lokalnej nawiązujące do form osuwiskowych. Na obszarze polskiej części Babiej Góry dominują liczebnie źródła stokowe, wypływające w większości z grubych pokryw koluwiów i w lejach źródłowych.
24 cm
Keywords: źródła; flisz; osuwiska; Babia Góra; Karpaty

Przegląd Geograficzny T. 63 z. 1-2 (1991) (IGiPZ PAN, 1991)
24 cm
Keywords: przestrzeń kulturowa; miasteczka rolnicze; bioklimat; typologie bioklimatu; temperatura radiacyjno-efektywna; osady jeziorne; antropopresja; elektrownie szczytowo-pompowe; telekomunikacja; erozja równin zalewowych; bilans cieplny ciała człowieka; pustynia Kara-kum; lodowce polarne; deglacjacja; geografia fizyczna; Spitsbergen; jezioro Gościąż; Jezioro Żarnowieckie

The dynamics of the timberline ecotone on the asymmetric ridge of the Babia Góra Massif, Western Carpathians - Czajka, Barbara; Łajczak, Adam; Kaczka, Ryszard J. (IGiPZ PAN, 2015)
Timberline ecotone (TE) generally developed because the temperatures in the environment were too low. There are other overlapping biotic and abiotic factors which affect the TE. The main aim of this work was to determinehow the asymmetry of Babia Góra’s ridge influences the location and characteristics of the timberline ecotone nowadays, and how the ridge influenced the timberline ecotone in the mid-20th century. The asymmetryof environmental conditions means the timberline has formed in two extreme environments: on the sunny and gentle southern slope (40% of the timberline length) and on the cold, humid, steep northern slope (another40% of the timberline length). The southern slope of the ridge shows a progressive timberline length of 86%. In turn, 81% of the timberline on the northern slope is in a stable ecotone.
24 cm
Keywords: Babia Góra; geomorfometria; asymetria grzbietu górskiego; przesuwanie się granicy lasu

The tree-ring growth responses to climate in the timberline ecotone of Babia Góra Mountain - Kaczka, Ryszard J.; Czajka, Barbara; Łajczak, Adam (IGiPZ PAN, 2015)
The growth/climate response of Norway spruce in the timberline ecotone of Babia Góra Mountain was examined. Based on a pool of 708 trees from 10 sites, the influence of age, exposure, and method of computingchronology, was assessed. Gridded data and 12 instrumental series were used to study the spatiotemporal relationship of the tree growth and climate. Temperature mainly controls the growth of the Norway spruce in thetimberline ecotone at Babia Góra Mountain. The most important factors were the June and July temperatures (r = 0.57) and of the entire growing season April-September (r = 0.52). The precipitation of late winter (Marchand correspondingly the January-March season) had a positive influence on the tree growth. The previously reported negative correlation with the summer precipitation was found but it was less important. The maturetrees growing on the northern slope showed a response to the summer temperature in a stronger manner than all the other groups. The low-frequency SPL chronologies (detrended using the cubic smoothing splinesmethod) performed better than the RCS (regional curve standardisation) of the high-frequency SPL. A strong correlation was found with Obidowa, the nearest located instrumental data (a distance of 35 km), and theHala Gąsienicowa, the station located at a similar elevation a.s.l. (1508 m a.s.l.), but also with the Krakow located farther away and at a lower elevation (237 m a.s.l.). The TRW/temperature correlation was temporallymost stable in the case of Zakopane.
24 cm
Keywords: Babia Góra; Karpaty; klimat; dendrochronologia; świerk norweski; przyrosty drzew

The timberline as result of the interactions among forest, abiotic environment and human activity in the Babia Góra Mt., Western Carpathians - Kaczka, Ryszard J.; Czajka, Barbara; Łajczak, Adam; Szwagrzyk, Jerzy; Nicia, Paweł (IGiPZ PAN, 2015)
The character and main natural and anthropogenic factors driving the timberline on the Babia Góra Mt. was discussed. The model of Holtmeier (2009) was modified to describe the functioning of the local timberline.Originating in a geological structure, the asymmetric shape of the ridge of the Babia Góra Mt. created consequences for most of the components of the environment of the timberline. This main stationary factor influenceall the others including the differences of local climate, soil development and human activity. The long history of direct impact of land use, grazing and logging and recent indirect influences (air pollution and climatewarming) control the present character of the timberline.
24 cm
Keywords: górna granica lasu; Karpaty; Babia Góra; wypas; przestrzenna i czasowa dynamika górnej granicy lasu

The influence of snow avalanches on the timberline in the Babia Góra Massif, Western Carpathians - Czajka, Barbara; Łajczak, Adam; Kaczka, Ryszard J. (IGiPZ PAN, 2015)
Avalanches are one of the most important abiotic factors influencing the timberline on a worldwide scale. In the case of Babia Góra, avalanches are found to affect more than ¹⁄³ of the length of the timberline, locally lowering it by as much as 350 m in distance. The timberline under the influence of avalanche processes is associatedwith steep slopes (>30°), with 90% of this being located on the massif’s northern slope. In the long run (1964-2009), around the whole massif the timberline shows a high degree of stability along 79% of itslength. It proved possible to reconstruct avalanche events along the largest avalanche path in the examined massif, the Szeroki Żleb gully. Nine such events are seen to have occurred over the past 120 years, with sevenof these characterising the last 50 years. The avalanche(s) occurring in winter 1975/1976 had the greatest impact on the timberline in the Szeroki Żleb gully over the examined period.
24 cm
Keywords: górna granica lasu; lawiny śnieżne; Babia Góra; świerk norweski; iterpretacja obrazu; dendrogeomorfologia

Zapis zmian klimatu w ostatnich 200 latach w morfodynamice stoków oraz kriosferze Tatr i Karkonoszy = A record of climate changes over the past 200 years in slope morphodynamics and the cryosphere of the Tatra and Karkonosze Mountains - Kędzia, Stanisław (IGiPZ PAN, 2017)
Zmiany klimatu w ciągu ostatnich 200 lat miały istotny wpływ na morfodynamikę stoków. Szczególnie odzwierciedliły się w aktywności spływów gruzowych, zarówno w Tatrach, jak i w Karkonoszach. Okresami największej aktywności spływów gruzowych w obu masywach górskich był koniec małej epoki lodowej oraz ostatnie 20-30 lat. Zmiany klimatu miały również duży wpływ na wielkość wieloletnich płatów śnieżnych, które największą miąższość osiągnęły, podobnie jak lodowce alpejskie, w małej epoce lodowej. Pomimo różnic klimatycznych pomiędzy Tatrami i Karkonoszami, związanych głównie z wysokością bezwzględną i położeniem geograficznym, zgodność przebiegu zmian omawianych w tej pracy procesów morfogenetycznych nawiązuje do stwierdzonej przez klimatologów i dendrochronologów równoleżnikowej telekoneksji.
24 cm
Keywords: Geografia -- czasopisma [KABA]; Polska -- geografia -- czasopisma [KABA]; Tatry; Karkonosze; kriosfera; spływy gruzowe

Geographia Polonica Vol. 80 No. 2 (2007) - Jania, Jacek (1950– ). Red.; Kundzewicz, Zbigniew (1950– ). Red. (IGiPZ PAN, 2007)
202 s. ; 24 cm
Keywords: zjawiska ekstremalne; meteorologia; hydrologia; klimat; prędkość wiatru; zagrożenia powodziowe; susze hydrologiczne; spływy gruzowe; opady ekstremalne; sztormy; Europa; Polska; Morze Bałtyckie

Promieniowanie słoneczne a gospodarka cieplna organizmu człowieka = Solar radiation and heat balance of human organism - Błażejczyk, Krzysztof (IGiPZ PAN, 1998)
82 s., [2] k. tabl. kolor. : fot., rys., wykr. ; 30 cm
Literatura s. 71-76
Streszcz. ang.
Keywords: Człowiek -- skutki promieniowania słonecznego -- modele matematyczne [KABA]; Promieniowanie słoneczne -- Polska -- obserwacje [KABA]; Promieniowanie słoneczne -- skutki fizjologiczne [KABA]; Termoregulacja [KABA]; bilans cieplny ciała człowieka; bioklimatologia

Differentiation of vertical limit of forest at the Babia Góra Mt., the Western Carpathian Mountains - Łajczak, Adam. Autor; Spyt, Barbara. Autor (IGiPZ PAN, 2018)
The work contains quantitative analysis of differentiation of altitudinal position and sinuosity of two lines determining the course of forest limit, i.e. timberline and treeline within Babia Góra Mt. (1725 m a.s.l.) homoclinal flysch ridge (the Western Carpathians). The course of the empiric timberline was delimited basing on aerial photographs with details from spatial data of Aerial Laser Scanning conducted in 2012. On the N slope, the course of timberline is exclusively conditioned by natural factors, whereas on the S slope this line was shifted downwards as a result of sheep and cattle grazing (however it has shown progression for the last 80 years). In the course of theoretical treeline conditioned by macrotopography and local climate, the mass-elevation effect is visible, and on the N slope, additionally, a sub-summit downward shift (the Diablak effect) occurs. The sequence of natural factors, according to their positive or negative influence on timberline and treeline courses was determined.
24 cm
Keywords: granica lasu; granica drzew; efekt masowej elewacji; homoklinalny grzbiet fliszowy; asymetria klimatyczna; lawiny śnieżne; Babia Góra; Karpaty Zachodnie

Wyniki badań bioklimatu Polski. Cz. 2 = Results of bioclimatic research of Poland - Kozłowska-Szczęsna, Teresa (1931– ). Red. (IGiPZ PAN, 1991)
83 s. : il. ; 24 cm
Gł. tabele
Bibliogr. s. 17-18
Streszcz. ang. i ros.
Keywords: Bioklimatologia -- obserwacje -- Polska -- 1945-1970 [KABA]; bioklimat

UTCI - nowy wskaźnik oceny obciążeń cieplnych człowieka = UTCI - new index for assessment of heat stress in man - Błażejczyk, Krzysztof; Broede, Peter; Fiala, Dusan; Havenith, George; Holmér, Ingvar; Jendritzky, Gerd; Kampmann, Bernhardt (IGiPZ PAN, 2010)
24 cm
Keywords: wskaźniki bioklimatyczne; bilans cieplny ciała człowieka; obciążenia cieplne; UTCI

Bioklimatyczne uwarunkowania rekreacji i turystyki w Polsce = Bioclimatic principles of recreation and tourism in Poland - Błażejczyk, Krzysztof (IGiPZ PAN, 2004)
291 s. : mapy, rys., wykr. ; 24 cm
Bibliogr. s. 262-276
Streszcz. ang.
Keywords: Bioklimatologia -- Polska [KABA]; Rekreacja -- Polska -- 1990- [KABA]; Turystyka -- Polska -- 1990- [KABA]; bioklimatyczne uwarunkowania turystyki; bioklimatyczne uwarunkowania rekreacji; bodźce klimatyczne; wskaźniki biometeorologiczne; wskaźniki bioklimatyczne; bilans cieplny ciała człowieka; modele bioklimatyczne; Menex_2002 (model bioklimatyczny); klasyfikacje pogody; regiony bioklimatyczne; Polska

Bioklimatyczna analiza warunków pogodowych w Polsce - Błażejczyk, Krzysztof (IGiPZ PAN, 1992)
24 s., [7] k. tabl. złoż. : mapy ; 30 cm
Literatura s. 24
Streszcz. ang.
Keywords: Pogoda [KABA]; Człowiek -- skutki oddziaływania klimatu -- Polska [KABA]; Pogoda -- ocena -- Polska [KABA]; klimat; bioklimat

Debris flow activity in the Slovak part of the High Tatras in the light of lichenometric dating - Kędzia, Stanisław. Autor; Hreško, Juraj. Autor; Bugár, Gabriel. Autor (IGiPZ PAN, 2023)
Rock walls and talus slopes, which are the most common features of high-mountain relief, have been researched for many years. Geomorphologists have taken particular interest in debris flows, which play a major role in the development of talus slopes. This paper presents the results of the first lichenometric dating of debris flows on the southern slopes of the Tatra Mountains. The greatest debris flow activity took place in the Little Ice Age and in the last two decades.
24 cm
Keywords: datowania lichenometryczne; spływy gruzowe; Tatry Wysokie

Aktywność spływów gruzowych w polskiej części Karkonoszy w świetle badań lichenometrycznych = The activity of debris flows in the Polish part of the Karkonosze Mountains in the light of lichenometric measurements - Kędzia, Stanisław; Parzóch, Krzysztof (IGiPZ PAN, 2016)
W latach 2011-2012 oraz 2014 r. prowadzono datowania lichenometryczne form utworzonych przez spływy gruzowe w karkonoskich kotłach polodowcowych: Wielkim Śnieżnym Kotle, Czarnym Kotle Jagniątkowskim, Kotle Małego Stawu, Kotle Łomniczki oraz niszy niwalnej Białego Jaru. Celem tych pomiarów było zbadanie aktywności spływów gruzowych w ostatnich 150 latach. Na podstawie przeprowadzonego datowania lichenometrycznego wydzielono trzy fazy aktywności spływów gruzowych w Karkonoszach. Pierwszą fazę, związaną z małą epoką lodową, charakteryzowała duża aktywność badanych procesów. Zakończyła się ona, podobnie jak w Tatrach, w latach 1920. Po niej nastał okres względnego spokoju, przerywany niewielką liczbą epizodów występowania spływów w latach 1930., 1940. i w roku 1964. Kolejna faza wzmożonej aktywności transportu materiału skalnego w obrębie form utworzonych przez spływy, włączając również nowe spływy gruzowe, rozpoczęła się w latach 1980. i trwa do dziś.
24 cm
Keywords: cyrki polodowcowe; spływy gruzowe; datowania lichenometryczne; Karkonosze